2018
DOI: 10.5812/aapm.74124
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Adding Magnesium Sulfate to Ropivacaine on Ultrasound-Guided Transverse Abdominis Plane Block After Abdominal Hysterectomy

Abstract: BackgroundPost-hysterectomy pain is extremely annoying and using transverse abdominis plane (TAP) block can be a useful method to manage postoperative pain, but its duration of effect is challenging. Magnesium sulfate increases, in some cases, the effects of local anesthetics on the peripheral nerve blocks.ObjectivesThe current study aimed at investigating the effects of adding magnesium sulfate to ropivacaine in the transverse abdominis plane block after hysterectomy.MethodsThe current randomized, double blin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 35 publications
2
29
0
Order By: Relevance
“…Ropivacaine has a greater degree of separation between the motor and sensory blockade than bupivacaine and it is used to relieve epidural pain during labor or for cesarean section (3,4,18,19). Adding auxiliary magnesium sulfate to ropivacaine does not increase the analgesic effect in the transversus abdominis plane block after hysterectomy (20). It is associated with a less central nervous system and other toxicities, especially cardiovascular toxicity.…”
Section: Introductionmentioning
confidence: 95%
“…Ropivacaine has a greater degree of separation between the motor and sensory blockade than bupivacaine and it is used to relieve epidural pain during labor or for cesarean section (3,4,18,19). Adding auxiliary magnesium sulfate to ropivacaine does not increase the analgesic effect in the transversus abdominis plane block after hysterectomy (20). It is associated with a less central nervous system and other toxicities, especially cardiovascular toxicity.…”
Section: Introductionmentioning
confidence: 95%
“…A wide range of medications including opioids, paracetamol, non-steroidal anti-inflammatory drugs (NSAIDs), gabapentin, pregabalin, tramadol, ketamine, and so forth, have been used alone or in combination to achieve this purpose ( 2 - 4 ). Beside systemic drugs, other anesthesia techniques including neuraxial techniques, transverse abdominis plane (TAP) block, wound injection, and intraperitoneal instillation have already been used for pain management after obstetric and gynecologic surgery ( 5 - 9 ). Paracetamol has limited effects to preclude and control post-caesarean pain ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Imani et al [7], to assess the effects of magnesium sulfate on intrathecal analgesia after hysterectomy, it was found that magnesium sulfate led to longer duration of analgesia after surgery and reduced postoperative analgesic requirement [7].…”
Section: Resultsmentioning
confidence: 99%